Penerapan Pembiasaan Baik Anti Perundungan di SMP Panca Budi Medan - M Khalid Wiwoko; Qaulan Raniyah (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
Bullying is a serious problem that can have a negative impact on student development, both physically and psychologically. This research aims to examine and analyze efforts to create good anti-bullying habits at Panca Budi Middle School in Medan. Using qualitative descriptive methods, this research explores the strategies and programs implemented in schools to create a safe and bullying-free school environment. Data was obtained through interviews with teachers, students, as well as observations in the field. The research results that the application of good habits as a form of implementing of PAI, such as socialization activities, psychological approaches, and intensive supervision, has succeeded in reducing bullying rates and creating a positive culture in schools.